Layanan Konseling Kelompok dengan Menggunakan Pendekatan Cognitive Behavior Teraphy (CBT) untuk Meningkatkan Penyesuaian Diri pada Siswa SMA: Array - Esi Zarisman; Netrawati; Yeni Karneli (eductum: Jurnal Literasi Pendidikan, 2022)
Children who have poor self-adjustment will find it difficult to establish relationships with friends, teachers and the school environment. As for some of the objectives of this study are to find out 1. An overview of the level of adjustment of high school students 2. The effect of the cognitive behavior therapy approach on the level of adjustment of students in high school. The results of the discussion show that self-adjustment has a very important role for students to be able to socialize with their surroundings and be able to take part in learning well. And students who lack self-confidence can be helped by group counseling with a cognitive behavior therapy approach. Where, CBT approach counseling is counseling that focuses on insight that emphasizes the process of changing negative thoughts and maladaptive beliefs that individuals have.